2005
DOI: 10.1542/peds.2004-2188
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Classification of Sudden Unexpected Infant Deaths: United States, 1992–2001

Abstract: The failure of the overall postneonatal mortality rate to decline in the face of a declining SIDS rate in 1999-2001 raises the question of whether the falling SIDS rate is a result of changes in certifier practices such that deaths that in previous years might have been certified as SIDS are now certified to other non-SIDS causes. The observation that the increase in the rates of non-SIDS causes of sudden unexpected infant death could account for >90% of the drop in the SIDS rates suggests that a change in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 19 publications
2
123
0
2
Order By: Relevance
“…Diagnostic shift 10,43 illustrates the complex interplay between medical science, forensic practice, and epidemiology. Although some changes in diagnostic preferences may reflect attitudes toward particular nomenclature, such as the use of "cause unknown" instead of "SIDS," others imply significant differences in the decision-making process for the classification of sudden infant deaths.…”
Section: Figurementioning
confidence: 99%
“…Diagnostic shift 10,43 illustrates the complex interplay between medical science, forensic practice, and epidemiology. Although some changes in diagnostic preferences may reflect attitudes toward particular nomenclature, such as the use of "cause unknown" instead of "SIDS," others imply significant differences in the decision-making process for the classification of sudden infant deaths.…”
Section: Figurementioning
confidence: 99%
“…Some researchers have suggested that some of the decline in reported sudden infant death syndrome deaths in the USA from 1999 to 2001 was related to changes in the way that these deaths were investigated, reported, and classified. (33,34) …”
Section: Systems To Record and Classify Deathsmentioning
confidence: 99%
“…Investigation of cause-and timing-specific mortality includes assessing trends in causes of death and changes in classification of death; comparing death rates among fetal, neonatal, and postneonatal periods over time; and assessing changes in cause and timing within categories of infant maturity. Definitions selected for use in a classification system for infant deaths and reliability of data for classification may also affect proportionate mortality [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Cause and Timing Of Infant Death: Definition And Methodsmentioning
confidence: 99%
“…Investigation of cause-and timing-specific mortality includes assessing trends in causes of death and changes in classification of death; comparing death rates among fetal, neonatal, and postneonatal periods over time; and assessing changes in cause and timing within categories of infant maturity. Definitions selected for use in a classification system for infant deaths and reliability of data for classification may also affect proportionate mortality [13][14][15][16][17][18][19][20][21][22][23].While several systems of classification of perinatal death exist [23][24][25][26][27][28], no single system has been adopted as a standard. Standardized systems exist including the International Statistical Classification of Diseases (ICD; series 9 and 10) codes, however, these classification systems are often cumbersome and complex.…”
mentioning
confidence: 99%